Postnatal development in a marsupial model, the fat-tailed dunnart (Sminthopsis crassicaudata; Dasyuromorphia: Dasyuridae) - Laura E. Cook (Nature Portfolio, 2021)
Cook, Pask and colleagues describe the ossification of the skull and forelimbs in the developing postnatal fat-tailed dunnart. As one of the most altricial marsupials at birth with a short reproductive cycle and simple lab husbandry, this species is a promising model organism for jaw and forelimb development in mammals.